Principal Leadership Strategies in Improving Teachers’ Performance Through Conflict Management and Strengthening Organizational Culture - Zainul Rifqi; Dessy Wardiah; Muhammad Juliansyah Putra (Yayasan Sembilan Pemuda Indonesia, 2027)
This study aims to analyze the principal’s leadership strategies in improving teachers’ performance through conflict management and strengthening organizational culture at SMP Negeri 35 Palembang. A qualitative case study approach was employed, utilizing observation, in-depth interviews, and documentation for data collection. Data were analyzed through interactive model procedures. Findings reveal that the principal’s strategies include open communication, problem clarification, deliberation, regulation enforcement, discipline, cooperation, routine supervision, and professional role modeling. Conflict factors stem from perceptual differences, ineffective communication, unequal task division, character variations, and high administrative burdens. Organizational culture strengthening is influenced by principal assertiveness, teacher commitment, clear rules, and a conducive work climate. Supporting factors include effective communication, teacher collaboration, consistent guidance, professional awareness, and firm regulations. Inhibiting factors comprise differing teacher responses to change, principal time constraints, administrative burdens, latent conflicts, and limited facilities. The integration of conflict management and culture strengthening positively impacts teacher performance through improved discipline, lesson planning quality, work motivation, and a more conducive environment. This study uniquely integrates conflict management and organizational culture strengthening as dual strategies within a single leadership framework in an Indonesian secondary school context. Principals are advised to develop communicative, participatory, and consistent leadership to create a harmonious and productive organizational culture. This research contributes empirical evidence that effective leadership strategies integrating conflict resolution and cultural reinforcement significantly enhance teacher performance, offering actionable insights for school leaders in similar urban secondary education settings.